Randomized Controlled Trial of a Couples-Based HIV Intervention for Transgender Women and Their Partners: Findings from the "It Takes Two" Project. - Gamarel, Kristi E.; Operario, Don; Stein, Ellen S.; Pollack, Lance M.; Neilands, Torsten B.; McCree, Breonna; Johnson, Jack; Correll-King, Wesley M.; Olem, David; Johnson, Mallory O.; Sevelius, Jae M. (AIDS & Behavior, 2025)
"It Takes Two" is a couples-based HIV prevention program designed for transgender women and their partners. The aim of this project is to alleviate HIV vulnerability by enhancing communication, improving shared goals, and decreasing relationship stigma. From November 2019 to November 2022, we conducted a randomized controlled trial with 52 couples (104 individuals). Participants were randomized into one of two groups: the intervention group received four 1-hour counseling sessions, while the control group received educational videos. Due to the COVID-19 pandemic, 60% of participants took part in a fully digital trial, including telehealth counseling. Assessments were conducted at baseline and at 3, 6, 9, and 12 months. We analyzed the outcomes using multilevel random coefficient models. While the intervention did not significantly impact HIV vulnerability, communication, or shared goals, there were reductions in relationship stigma among partners of transgender women at 3- (Cohen's d = 0.54), 6- (Cohen's d = 0.57), and 12-months (Cohen's d = 0.72) post-intervention. These findings highlight the importance of addressing relationship stigma and involving partners in HIV prevention efforts to promote the health of transgender women.